Children of the 21st century the first five years - Hansen, Kirstine ca. 20./21. Jh; Joshi, Heather 1946-; Dex, Shirley 1950- (UK millennium cohort study series, 2010)
This book documents the first five years of life of the children of the influential Millennium Cohort Study, looking at the children's lives and development as they begin formal education and the implications for family policy, and service planning in health and social services